Vazão máxima em pequena bacia hidrográfica parcialmente urbanizada em Uberlândia – MG - Martins, Lorraine Campos (2017)
The maximum flow is defined as the flow reached when the entire watershed contributes to the increase in flow, which exceeds the usual flow values in a certain watercourse. The concept of maximum flow is associated with some risk to be matched or exceeded. The maximum flow rate is a parameter widely used in hydraulic works calculations. Therefore, the objective of this work is to estimate the maximum flow rate in the Glória Stream Experimental Watershed located in the city of Uberlândia - MG, through estimation methods mentioned in the literature, and to generate a mathematical model capable of estimating with relative accuracy the flow Maximum from some observed parameters. In addition, the work aimed at comparing the results obtained through these methods to the values observed directly in the river watershed, in order to verify the effectiveness of such methods. All the data necessary to carry out this research, such as the flow, rainfall, use and soil type measurements were made in the Glória Stream Experimental Watershed, in the Araguari River sub-watershed, in Minas Gerais, Brazil. For the estimation of the maximum flow, the rational and triangular unit hydrograph were used. In this work, the calculation of the concentration time was made from three different methodology and consecrated in the technical literature. The results obtained by these methods were compared with the maximum flow values observed in 14 hydrograms obtained in the control section of the experimental watershed. Precipitation data were also obtained directly in the watershed, and based the calculation of important variables in this research, such as effective precipitation and direct surface runoff. From the precipitation data, an equation was generated able to estimate the maximum flow in the experimental watershed. The results obtained showed that the methods mentioned in the literature tend to overestimate the maximum flow, mainly the Rational method. It was also observed that the maximum flow values obtained by applying the unit hydrograph method were more consistent with the observed values. The equation obtained to estimate the maximum flow in the experimental basin was generated from direct surface flow, obtained by means of the trapezoid rule. The maximum flow values obtained by this equation approximated considerably the observed values, obtaining 0.95 for the Nash-Sutcliffe coefficient, which indicates a good fit of the model.